The Troika of Adult Learners, Lifelong Learning, and Mathematics Learning from Research, Current Paradoxes, Tensions and Promotional Strategies - Safford-Ramus, Katherine; Misra, Pradeep Kumar; Maguire, Terry (ICME-13 Topical Surveys,, 2016)
This book presents a synopsis of six emerging themes in adult mathematics/numeracy and a critical discussion of recent developments in terms of policies, provisions, and the emerging challenges, paradoxes and tensions. It also offers an extensive review of the literature adult mathematics education. Why do adults want to learn mathematics? Did they enjoy mathematics at school so much that they want to continue? NO! Most of these adults have to learn mathematics because it is part of a formal qualification they need, because their job demands the ability to apply mathematics, or because they need basic numeracy in their daily lives. Lastly, the authors discuss five potential strategies to promote lifelong learning of mathematics among adult learners.